The Implementation of Islamic Education Values in the Customs of Tunggu Tubang Semende at Manggarai Village - Ambarwati, Julia; Setiawan, Dedi; Anwar, M. Saidun (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2025)
The Wai Tubang custom is a matrilineal inheritance system in Semende society, where inheritance is passed on to the eldest daughter. This research aims to analyze the implementation of Islamic educational values in the Tunggu Tubang custom and its impact on the character education of the younger generation of Semende. The research method used is qualitative with a descriptive approach. Data was collected through observation, in-depth interviews and documentation of traditional stakeholders, religious leaders and local communities. The research results show that the Tunggu Tubang custom contains Islamic educational values, such as responsibility, justice, trust, and social care. The implementation of these values is reflected in the role of Wait Tubang children in maintaining family harmony, caring for inheritance, and guiding other family members. Supporting factors in implementing this custom include the strong influence of the Islamic religion and the role of customary holders, while the main challenge is social and economic change which causes a shift in values in society. Overall, the Tunggu Tubang custom contributes to the character formation of the younger generation of Semende by instilling Islamic educational values in everyday life. Therefore, efforts to preserve this custom need to be supported by an approach that is in line with current developments, so that it remains relevant in building individual character based on Islamic values.